Jane Allen, Junior - Bancroft, Edith (Salt Lake City, UT : Project Gutenberg, 2004)
"Jane Allen, Junior" by Edith Bancroft is a novel likely written in the early 20th century. The book centers around the character Jane Allen, a junior at Wellington College, exploring her relationships and challenges as she navigates school life with her friends, including Judith and Dozia. The story blends themes of friendship, personal growth, and the trials associated with college life, creating a vibrant picture of youthful exuberance and social dynamics. The beginning of the book unfolds on a warm September day as the students at Wellington College prepare for the new school year. Jane and her friends gather under a poplar tree, discussing the start of classes and their apprehensions about new arrivals, particularly a freshman named Shirley Duncan who seems destined to cause a stir. Amidst chatter about school duties and the antics of their peer group, Jane's friends notice something is off with her, hinting at a deeper conflict in Jane's mind. As the chapter progresses, a sense of camaraderie develops among the girls, setting the stage for various misadventures and interpersonal conflicts as they navigate their roles in college. The narrative hints at drama ahead, particularly with the arrival of new students and the potential implications of the scholarship Jane inadvertently associated with a girl from a different social stratum. (This is an automatically generated summary.)
Release date is 2004-01-01
Produced by Charles Franks and the Online Distributed Proofreading Team
Keywords: College students -- Juvenile fiction; Young women -- Juvenile fiction; Women college students -- Juvenile fiction; Basketball stories